The Effect of Giving Education on Knowledge of Self-Medications for Dysmenorrhea in Students of Vocational High School Muhammadiyah 03 Metro - Ulfa, Rida; Kartika Putri, Diah; Yanti, Erna; Sania Rosanti, Afi (LPPM Universitas Dhyana Pura, 2025)
Women frequently suffer from menstrual abnormalities, such as dysmenorrhea, which primarily affects teenagers. Teenagers who experience dysmenorrhea at school may engage in less educational activities. Adolescent dysmenorrhea self-medication behaviour will be impacted by ignorance. The study objective was to determine the knowledge of self-medication for dysmenorrhea before and after education, and to determine the effect of education on knowledge of self-medication for dysmenorrhea. This study is a quantitative study with a quasi-experimental design method of non-equivalent control group. Sampling with proportion sampling with inclusion and exclusion criteria with a sample size of 82 respondents. The data analysis used the Wilcoxon and Mann-Whitney tests. The average pre-test value was 30.5% (good category), and the post-test was 65.9% (good category). The results of the Wilcoxon test obtained the Asymp. Sig (2-tailed) value in the treatment group 0.000 <0.05, stating that there was a difference in the level of knowledge before and after education was given. The Asymp. Sig (2-tailed) value in the control group obtained a value of 0.235> 0.05, so it was stated that there was no difference in knowledge in the pre-test and post-test. The results of the Mann-Whitney test showed that there was an effect of education on knowledge before and after education with an Asymp. Sig (2-tailed) value of 0.000 <0.05. Providing education with the lecture method and interactive discussion using video media related to self-medication for dysmenorrhea provided an increase in knowledge medication for dysmenorrhea in female students of Vocational High School Muhammadiyah 03 Metro with a p-value of 0.000 <0.05. related to self-medication for dysmenorrhea. There was an effect of providing education on knowledge of self-medication for dysmenorrhea in female students of Muhammadiyah 03 Metro Vocational School with a p-value of 0.000<0.05.